2012
DOI: 10.1183/09031936.00119111
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and respiratory symptoms in pre-school children: the Generation R Study

Abstract: Overall diet in early childhood may affect the development of respiratory symptoms. This study examined whether childhood dietary patterns are associated with respiratory symptoms in Dutch pre-school children, and whether this association could be explained by energy intake.A prospective cohort study was performed in 2,173 children aged f4 yrs. Data on asthma-related symptoms were obtained by questions from the age-adapted version of the "International Study of Asthma and Allergies in Childhood" questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
(45 reference statements)
1
40
3
Order By: Relevance
“…2 Indeed, we have previously found that a "Westernlike" dietary pattern in toddlers was associated with asthmalike symptoms at preschool age. 3 In contrast, we did not find any association with a dietary pattern characterized by high intake of fish, vegetables, and fruit 3 whereas adherence to this diet during pregnancy or at school age has been noted to protect against asthma in previous studies. [4][5][6][7][8] Because we did not find a clear association between a dietary pattern including fish and asthmalike symptoms, 3 we hypothesized that any potential beneficial effect of fish consumption in toddlers may be diluted in our previous study as a result of the dietary pattern approach and therefore deserves additional study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…2 Indeed, we have previously found that a "Westernlike" dietary pattern in toddlers was associated with asthmalike symptoms at preschool age. 3 In contrast, we did not find any association with a dietary pattern characterized by high intake of fish, vegetables, and fruit 3 whereas adherence to this diet during pregnancy or at school age has been noted to protect against asthma in previous studies. [4][5][6][7][8] Because we did not find a clear association between a dietary pattern including fish and asthmalike symptoms, 3 we hypothesized that any potential beneficial effect of fish consumption in toddlers may be diluted in our previous study as a result of the dietary pattern approach and therefore deserves additional study.…”
Section: Discussioncontrasting
confidence: 89%
“…Nonetheless, we have previously demonstrated that timing of introduction of food allergens and a dietary pattern including fish, vegetables, and fruit at age 14 months were not significantly associated with asthmalike symptoms in our cohort. 3,41 Also, the timing of introduction of fish showed no similarities with timing of introduction of other foods (Supplemental Table 9). This raises questions as to whether confounding by other diet factors plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the authors reported that the dietary pattern that included fast food, soda, and artificial juice was associated with respiratory infections and wheezing in Japanese adolescents. A positive association of the Western dietary pattern and symptoms of asthma was reported in the Netherlands, 42 Saudi Arabian, 43 New Zealand, 13 Sweden, 14 and Chinese 44,45 children. Although the role for food-based saturated fat in the risk of wheezing and asthma remains inconclusive, the effects of other specific nutrients (eg, antioxidant vitamins A, C, and E and selenium) have been reported associated with a higher prevalence of wheezing and asthma.…”
Section: Dietary Patterns and Risk Of Asthma Symptomsmentioning
confidence: 92%
“…The association between diet and childhood asthma is moderate, at best, with observational studies reporting 'protective' associations for fruits and vegetables, and fish intake [11,22]. To our knowledge, only one longitudinal study on dietary patterns and asthma has been published and reported a small positive association between adherence to a Western diet and incident wheezing in children [23]. Regarding diet during adulthood, the few longitudinal studies show, overall, no association [11].…”
Section: Diet and Asthma: Primary Preventionmentioning
confidence: 95%